Community-Based Exercise in the Context of HIV: Factors to Consider when Developing and Implementing Community-Based Exercise Programs for People Living with HIV. (May 2017) - Li, Anna; McCabe, Taylor; Silverstein, Erin; Dragan, Stephanie; Salbach, Nancy M.; Zobeiry, Mehdi; Beldick, Sarah; Godi, Chris; O'Brien, Kelly K.
Objective: To identify factors to consider for developing and implementing a community-based exercise (CBE) program for people living with HIV (PLWH). Methods: We conducted a qualitative descriptive study using semi-structured interviews with PLWH, rehabilitation professionals, and recreation providers from Canada and the United Kingdom. We asked participants to describe their experience with exercise, facilitators, and barriers to accessing and participating in exercise, and factors to consider in developing a CBE program for PLWH. Interviews were analyzed using content analytical techniques. Results: We developed a Framework of CBE in the Context of HIV that describes (1) exercise experiences of PLWH (nature of exercise, motivators for initiating or sustaining exercise, perceived benefits, and barriers and facilitators to exercise) and (2) 11 factors to consider in developing and implementing a CBE program for PLWH. Conclusion: Recommendations for the development and implementation of an accessible and feasible CBE program may enhance exercise participation among PLWH.